Multilayered artifacts in the pre-Columbian metallurgy from the North of Peru Multilayered artifacts in the pre-Columbian metallurgy from the North of Peru - Cesareo, R (2013)
This work was partially supported by a bilateral project between the Consiglio Nazionale delle Ricerche and Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica of Peru (CNR-CONCYTEC, 2009-2011 and 2012-2014). F. Lopes acknowledges CAPES for a 7 months grant at the University of Sassari.